Experimentally examination of thyristor controlled braking resistor (TCBR) - Ayık, Mehdi; Gelen, Ayetül (Institute of Electrical and Electronics Engineers Inc., 2021)
In this paper, it is aimed to examine the behavior of Thyristor Controlled Braking Resistor (TCBR), which is one of the (Flexible Alternating Current Transmission System) FACTS types, in wind energy conversion systems containing synchronous generator. TCBRs often involve the use of shunt coupled braking resistors to correct the temporary imbalance between the mechanical power input and the electrical power output of the generators. In principle, small frequency oscillations can be damped by applying a controllable resistor insertion method to the power system. Within the scope of this paper, the performance of the system is evaluated by using TCBR in a short circuit fault in a three-phase wind energy based power system. According to the results obtained from the experimental studies, the excessive oscillations in the speed of the generator together with the failure reached their nominal values in a short time with the activation of the TCBR.
Keywords: experiment; FACTS; fault; power systems; TCBR